2013
DOI: 10.1186/1471-2482-13-s2-s13
|View full text |Cite
|
Sign up to set email alerts
|

Is the advanced age a contraindication to GERD laparoscopic surgery? Results of a long term follow-up

Abstract: BackgroundIn this prospective non randomized observational cohort study we have evaluated the influence of age on outcome of laparoscopic total fundoplication for GERD.MethodsSix hundred and twenty consecutive patients underwent total laparoscopic fundoplication for GERD. Five hundred and twenty-four patients were younger than 65 years (YG), and 96 patients were 65 years or older (EG). The following parameters were considered in the preoperative and postoperative evaluation: presence, duration, and severity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 56 publications
0
16
0
Order By: Relevance
“…Similar results have been shown in some earlier studies, 9,25 although other investigations have found contradictory results. 26,27 The consequence of comorbidities on the rate of recurrence of GERD after laparoscopic antireflux surgery has, to the best of our knowledge, not been studied before. It is possible that the increased risk of reflux recurrence associated with older age and comorbidities exists because only patients with particularly severe and refractory GERD in these groups are selected for surgery, and these patients might also be at a higher risk of recurrence of reflux.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results have been shown in some earlier studies, 9,25 although other investigations have found contradictory results. 26,27 The consequence of comorbidities on the rate of recurrence of GERD after laparoscopic antireflux surgery has, to the best of our knowledge, not been studied before. It is possible that the increased risk of reflux recurrence associated with older age and comorbidities exists because only patients with particularly severe and refractory GERD in these groups are selected for surgery, and these patients might also be at a higher risk of recurrence of reflux.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the medical costs among elderly patients in both groups were not significantly different. A study by Fei et al [27] showed that the number of atypical symptoms was higher in the elderly, and the number of typical symptoms was higher in younger patients. In addition, elderly patients are more likely to have poor motility of the esophagus (dysmotility), which is predicted to be insignificant after antireflux surgery.…”
Section: Discussionmentioning
confidence: 98%
“…Several studies have shown the safety and excellent results for LARS also in elderly patients. [ 8 10 19 20 21 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 6 7 8 ] Hence, it can be argued that age should not be a contraindication to LARS. However, there are few reports that have evaluated the long-term results after 5 years or more[ 9 10 ] in the elderly patients, after LARS. In this study, we examined the effects of age on the immediate operative outcome and complications of LARS (Nissen fundoplication) in a prospective fashion.…”
Section: Introductionmentioning
confidence: 99%